Everywoman her own theology : on the poetry of Alicia Suskin Ostriker - Smith, Martha Nell, 1953-; Enszer, Julie R., 1970- (Under discussion., 2018)
"Alicia Ostriker's artistic and intellectual productions as a poet, critic, and essayist over the past 50 years are protean and have been profoundly influential to generations of readers, writers, and critics. In all her writings, both the feminist and the human engage fiercely with the material and metaphysical world. Ostriker is a poet concerned with questions of social justice, equality, religion, and how to live in a world marked by both beauty and tragedy. Everywoman Her Own Theology: On the Poetry of Alicia Suskin Ostriker engages Ostriker's poetry from throughout her career, including her first volume Songs, her award-winning collection The Imaginary Lover, and her more recent work in the collections No Heaven, the volcano sequence, The Old Woman, the Tulip, and the Dog, and Waiting for the Light. Like her literary criticism and essays, Ostriker's poetry explores themes of feminism, Jewish life, family, and social justice. With insightful essays-some newly written for this collection-poets and literary critics including Toi Derricotte, Daisy Fried, Cynthia Hogue, Tony Hoagland, and Eleanor Wilner illuminate and open new pathways for critical engagement with Alicia Ostriker's lifetime of poetic work."